Social Justification, Social Control and Social Development - M. Guffar Harahap; Muhammad Hizbullah; Haidir Haidir (Universitas Islam Negeri Sumatera Utara, 2021)
Law as provisions and norms that have special characteristics such as protecting, regulating and providing balance in maintaining the public interest. Therefore, violating legal provisions that cause harm from someone's negligence and cause interference with the public interest can cause reactions from. Provisions that apply to someone who neglects and disturbs the balance of the public interest are legal provisions that apply in the life of social groups at that time, not past legal provisions that have been in force or are being planned to come into effect. This study aims to see the law as a social justification, social control and social empowerment so that it can present a law based on justice. This research uses qualitative research methods with literature studies, namely by collecting data through reference books, journals, scientific articles and others. The conclusions of this study are 1) law is a tool for realizing and creating peace in social life and a means for realizing social justice, both birth and bathing as well as driving development for the community. 2) As a social tool, law means something that can determine human behavior where the law tries to direct people to behave properly in accordance with the rules so that peace and control are realized. 3) Positive impacts as social engineering can change certain patterns in a society, both in the sense of strengthening a habit into something more believed, as well as in the form of other changes. automatically there will be people who agree and disagree and then see what is happening in society, so that there are people who violate the law and so on